Kajian Yuridis Bentuk Tindak Pidana Pemerasan dan Pengancaman - Sapriani, Resky; Mannan, Khaerul; Darwis, Muhammad; Hibbu, Firmansyah; Andi Sapada, Rachman Rizal (Jurnal Litigasi Amsir, 2025)
This research aims to understand the judge's considerations in delivering a verdict on the criminal acts of extortion and threats in decision number 205/Pid.B/2021/PN.Pre and to determine the application of substantive law to the criminal acts of extortion and threats in decision number 205/Pid.B/2021/PN.Pre. This research employs a normative legal research approach. The research findings indicate that the basis for the judge's considerations in imposing a criminal verdict on the Defendant in decision number 205/Pid.B/2021/PN.Pre is in accordance with both juridical and non-juridical aspects. The panel of judges considered imposing criminal sanctions based on the indictment by the Public Prosecutor, which applied Article 335 Paragraph (1) Clause 1 of the Indonesian Criminal Code (KUHP) regarding the criminal act of threats. Therefore, the author agrees that the imposition of criminal sanctions against the Defendant is appropriate and sufficiently deterrent to the perpetrator. The application of substantive criminal law by the judge against the perpetrator of the criminal act in Decision Number 205/Pid.B/2021/PN.Pre was accurate. The Public Prosecutor used a single charge, namely the first charge, which violated Article 335 Paragraph (1) Clause 1 of the Indonesian Criminal Code (KUHP) concerning the criminal act of threats. Among the elements of the Article charged by the Public Prosecutor, it was proven beyond a reasonable doubt that the Defendant's actions fulfilled the elements of Article 335 Paragraph (1) Clause 1 of the Indonesian Criminal Code (KUHP) regarding the criminal act of threats.